A Role of Newly Found Auxiliary Site in Phospholipase A1 from Thai Banded Tiger Wasp (Vespa affinis) in Its Enzymatic Enhancement: In Silico Homology Modeling and Molecular Dynamics Insights - Withan Teajaroen; Suphaporn Phimwapi; Jureerut Daduang; Sompong Klaynongsruang; Varomyalin Tipmanee; Sakda Daduang (Toxins, 2020)
Phospholipase A1 from Thai banded tiger wasp (Vespa affinis) venom also known as Ves a 1 plays an essential role in fatal vespid allergy. Ves a 1 becomes an important therapeutic target for toxin remedy. However, established Ves a 1 structure or a mechanism of Ves a 1 function were not well documented. This circumstance has prevented efficient design of a potential phospholipase A1 inhibitor. In our study, we successfully recruited homology modeling and molecular dynamic (MD) simulation to model Ves a 1 three-dimensional structure. The Ves a 1 structure along with dynamic behaviors were visualized and explained. In addition, we performed molecular docking of Ves a 1 with 1,2-Dimyristoyl-sn-glycero-3-phosphorylcholine (DMPC) lipid to assess a possible lipid binding site. Interestingly, molecular docking predicted another lipid binding region apart from its corresponding catalytic site, suggesting an auxiliary role of the alternative site at the Ves a 1 surface. The new molecular mechanism related to the surface lipid binding site (auxiliary site) provided better understanding of how phospholipase A1 structure facilitates its enzymatic function. This auxiliary site, conserved among Hymenoptera species as well as some mammalian lipases, could be a guide for interaction-based design of a novel phospholipase A1 inhibitor.